Resident Stress Level during Steps of Cataract Surgery - Rali, Aditya; Fontus, Jerry; Ward, Laura; Aaron, Maria; Jones, Jeremy; Moore, Elliot; Khalifa, Yousuf M. (Journal of Academic Ophthalmology, 2018)
Purpose To investigate intraoperative stress levels using heart rate monitoring during each step of cataract surgery.Setting Single tertiary hospital.Design Observational study recording resident heart rate as a measure of acute stress level during cataract surgeries.Methods Emory ophthalmology postgraduate year (PGY) 3 and PGY-4 residents operating at Grady Memorial Hospital during the time period of the study were eligible to participate. Chest-strapped Bluetooth devices recorded heart rate during the surgeries. The mean, maximum, and minimum heart rates were then analyzed individually for the following steps of surgery: incisions, continuous curvilinear capsulorhexis, hydrodissection, nucleus disassembly, quadrant removal, cortical cleanup, intraocular lens insertion, and closure. Data collection started in April 2017 and ended in February 2018.Results Out of the 549 surgeries recorded, 427 yielded viable data. Across that dataset, quadrant removal had the highest adjusted mean heart rate value (90.3; 95% confidence interval [CI]: 82.9–97.7; p < 0.0001), highest adjusted maximum heart rate value (97.3; 95% CI: 89.5–105.3; p < 0.0001), and highest adjusted minimum heart rate value (82.1; 95% CI: 75.2–89; p < 0.0001). Nuclear disassembly and incisions were second and third highest, respectively.Conclusions Quadrant removal, nucleus disassembly, and incisions are the three most stressful steps for resident surgeons. This knowledge should be applied to enhance the resident experience by emphasizing these steps during surgical preparation and training. Future studies using intraoperative heart rate monitoring may be warranted to better understand the resident and attending experience and ultimately improve surgical outcomes.
Keywords: cataract; training; residents; residency; stress; heart rate; steps